TRANS-ARTERIAL EMBOLIZATION WITH N-BUTYL CYANOACRYLATE GLUE FOR RENAL BLEEDING: Case Report - Young, Benny (BALI MEDICAL JOURNAL; Vol 3 No 2 (2014), 2014)
Background: The objectivity in management of renal bleeding is to preserve a significant renal  parenchyma tissue and prevent associated morbidities like anemic shock or renal impairment from  substantial nephron demise or obstructed uropathy. Trans-arterial embolization therapy by  interventional radiology offers a high success rate with potential of reserving normal renal tissue. The  selection material for renal arterial embolization largely depends on vasculature anatomy and endpoint of procedure. N-butyl cyanoacrylate glue in our experience is applied in lesion supplied by  small size of end-artery.
Keywords: renal artery embolization, N-butyl cyanoacrylate glue, renal bleeding